The Citizen as Contributor—Letters to the Editor in the Austrian Tabloid Paper Kronen Zeitung (2008–2017). (10th June 2020) - Hayek, Lore; Mayrl, Manuel; Russmann, Uta
ABSTRACT: This paper addresses the subject of letters to the editor as one of the longest standing forums for public discussion and debate by ordinary citizens. To show how the voice of ordinary citizens is presented in letters to the editor during national election campaigns over a period of ten years (2008, 2013 & 2017), we are focusing on the Austrian Kronen Zeitung: A newspaper with an exceptionally high market share of up to 40% during the examination period, a heavy focus on the letters section with three pages per day, and a self-declared willingness to take a stance, especially during election periods. Based on a quantitative content analysis of 530 letters to the editor and 525 articles in the politics section as well as survey data from the Austrian national election study on the political positions of the Kronen Zeitung's readers, we find that letters to the editor in the Kronen Zeitung do not reflect, but complement the articles in the politics section. The tone of the letters is more negative than that of news articles, but the letters closely reflect the readers' political positions, therefore offering identification with the paper.